Age differences in the association of obstructive sleep apnea risk with cognition and quality of life. (2nd September 2013) - Addison‐Brown, Kristin J.; Letter, Abraham J.; Yaggi, Klar; Mcclure, Leslie A.; Unverzagt, Frederick W.; Howard, Virginia J.; Lichtman, Judith H.; Wadley, Virginia G.
Summary Using a sample of 2925 stroke‐free participants drawn from a national population‐based study, we examined cross‐sectional associations of obstructive sleep apnea (OSA) risk with cognition and quality of life and whether these vary with age, while controlling for demographics and comorbidities. Included participants from the REasons for Geographic And Racial Differences in Stroke (REGARDS) study were aged 47–93 years. OSA risk was categorized as high or low based on responses to the Berlin Sleep Questionnaire. Cognitive function was assessed with standardized fluency and recall measures. Depressive symptoms were assessed with the four‐item Center for Epidemiologic Studies Depression Scale. Health‐related quality of life (HRQoL) was assessed with the Medical Outcomes Study Short Form‐12 (SF‐12). Multivariate analyses of covariance (mancova) statistics were applied separately to the cognitive and quality of life dependent variables while accounting for potential confounders (demographics, comorbidities). In fully adjusted models, those at high risk for OSA had significantly lower cognitive scores (Wilks' lambda = 0.996, F3, 2786 = 3.31, P < 0.05) and lower quality of life [depressive symptoms and HRQoL] (Wilks' lambda = 0.989, F3, 2786 = 10.02, P < 0.0001). However, some of the associations were age‐dependent. Differences in cognition and quality of life between those at high and low obstructive sleep apnea risk were most pronounced during middle age, with attenuated effects after age 70 years.